PENERAPAN AKTIVITAS QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX.4 SMP NEGERI 22 PEKANBARU - Afrina, Noni Afrina; Heleni, Susda Heleni; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is classroom action research that aims to improve learning process and mathematics achievement with applying Quick on the Draw activity in cooperative learning type STAD. The subject of this research is student of class IX.4 SMP Negeri Pekanbaru in the first semester academic years 2014/2015, there are 34students in the class, consist of 13 boys and 21 girls. This researchis exercised in two cycles, and at the end of every cycle carried out mathematics achievement test. Data collected through observation and mathematics achievement test. The qualitative analysis descriptive narrative showed an improvement of learning process prior to the action of the first cycle to the second cycle. Then theresult of this research showed an increase in students from the base score with the percentage 8.82% to 20.59% on the first test and 64.71% on the second test. The results of the analysis concluded that Quick on the Draw activity in cooperative learning type STAD can improve the students learning achievement at class IX.4 SMP Negeri 22 Pekanbaru in the first semester academic years 2013/2014. Keywords: Mathematics Achievement, Quick on the Draw Activity, Cooperative Learning Type of STAD, Class Action Research